Construction and Effectiveness of Scoop Light Fishing (SLF) in Bero Village, West Muna, Southeast Sulawesi, Indonesia - Bubun, Rita L; Haini, Nukhra; Mahmud, Amir; Hamka, Eddy; Fadillah, Sitti; Saputra, Arif; Jaya, Timang; Widiono, Rayon; Astuti, Indah Ayu; Djohansyah, Erdiah Ramadani; Wahyudin, Aswan; Usman, Abdul Hamid; Listianto, Firgiawan (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2026)
The Scoop Light Fishing (SLF) gear is an innovative fishing technology capable of producing catches exceeding one ton per trip. Despite its high productivity and ability to operate during all lunar phases, including bright-moon periods, its construction and effective fishing time have not been scientifically assessed. The purpose of this study is to examine the construction of the SLF and identify its effective fishing period in the waters of Bero Village, Pulau Tiga, West Muna Regency. The research employed a survey method, with data collected through direct observation and interviews, and analyzed using qualitative and quantitative approaches. Quantitative analysis included a normality test and a one-way ANOVA at the 0.05 significance level, followed by an LSD post hoc test. The results show that the SLF consists of two main components: an elongated scoop-net bag directly connected to the fish hold and a square lighting system comprising four panels equipped with white and yellow lights, producing a total output of 4,765 watts. The SLF operates effectively during all lunar phases; however, fishing effectiveness is highest during the full moon phase (Q.III), as indicated by a significance value of less than 0.05. Keywords:   Effectiveness; moon phases; scoop light fishing